Positive Transformation of Islamic Law in Local Wisdom in the Sultan of Tidore - Harun Ginoni; Fauzan Hanafi; Nur Azizah Rahman (IAIN Manado, 2021)
Tidore is one of the Islamic Sultanates in the archipelago which applies Islamic Law positively from 1495 until the joining of Tidore into the lap of the Republic of Indonesia. Islamic law in the Tidore Sultanate is no longer applied as positive law but has become a value that lives with the customs of the people of the Tidore Sultanate. This research focuses on examining the transformation of the Islamic law that once prevailed in the Tidore sultanate into values, principles, and philosophies that live in the Tidore community. This research was built with a qualitative research type with a socio-historical approach involving traditional and religious leaders as resource persons and a study of the existing